2016
DOI: 10.1108/jfm-09-2014-0031
|View full text |Cite
|
Sign up to set email alerts
|

Shared student residential space: a post occupancy evaluation

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 16 publications
4
24
1
Order By: Relevance
“…Kaya and Erkip (2001) concluded that the students felt that the room sizes were larger and less crowded on the upper floors compared to the lower floors. Middle flats are the most preferred for use due to ease of accessibility and fewer noise problems (Khajehzadeh & Vale, 2014). In addition to building floor organizations, interior designs and density of the used furniture elements in the room's effect on students' satisfaction (Yildirim & Uzun, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kaya and Erkip (2001) concluded that the students felt that the room sizes were larger and less crowded on the upper floors compared to the lower floors. Middle flats are the most preferred for use due to ease of accessibility and fewer noise problems (Khajehzadeh & Vale, 2014). In addition to building floor organizations, interior designs and density of the used furniture elements in the room's effect on students' satisfaction (Yildirim & Uzun, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The provided service quality does not result in serious complaints from the students, similarly to the condition of some students in some dormitories in Iran (Khajehzadeh, 2016). Nevertheless, the provision of a quality of service, based on a well-prepared program, is essential to stimulate learners' loyalty and behavioral intention (Khoo, Ha, & McGregor, 2017).…”
Section: Dormitory Services Programmentioning
confidence: 99%
“…6 In order to avoid this situation, the research group focuses on the definition of an innovative multidisciplinary and multi-scale strategy, able to foster a reciprocity among academic knowledge, technical apparatus and local fragilities, fostering a shared environmental and social atmosphere as the condition for promoting a sense of belonging for individuals to their urban context and local community. According to international studies and experimentations (Ferrante 2012;Hassan et al 2012;Khajehzadeh and Brenda 2016;Kader 2017), this approach could produce significant consequences for urban territories, also in view of the participation and sensibilization of local people on urgent topics such as social integration, environmental sustainability, food education, waste reduction, sustainable mobility ( Fig. 3).…”
Section: The Case Of the Politecnico DI Milanomentioning
confidence: 99%